2014
DOI: 10.1115/1.4028075
|View full text |Cite
|
Sign up to set email alerts
|

Void Detection in Dielectric Films Using a Floating Network of Substrate-Embedded Electrodes

Abstract: A sensor is developed for simple, in situ characterization of dielectric thermal interface materials (TIMs) at bond line thicknesses less than 100 lm. The working principle is based on the detection of regions of contrasting electric permittivity. An array of long, parallel electrodes is flush-mounted into each opposing substrate face of a narrow gap interface, and exposed to the gap formed between the two surfaces. Electrodes are oriented such that their lengthwise dimension in one substrate runs perpendicula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The efficacy of such an approach has been demonstrated for the detection of dielectric anomalies in a 25 μm interfacial gap [15]. While the orthogonal mesh concept cannot be readily implemented in a TTV, an alternative concept is proposed which is more conducive to this implementation.…”
Section: Capacitive Sensor Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of such an approach has been demonstrated for the detection of dielectric anomalies in a 25 μm interfacial gap [15]. While the orthogonal mesh concept cannot be readily implemented in a TTV, an alternative concept is proposed which is more conducive to this implementation.…”
Section: Capacitive Sensor Conceptmentioning
confidence: 99%
“…With this demonstration, both bond layer thickness and void content have been successfully characterized using the algorithm. It is noted that in previous work, 15 grayscale void fraction maps such as Figure 6c have been used to generate a pseudo-high-resolution binary image of the estimated void shape, [18].…”
mentioning
confidence: 99%
“…When the gap is filled with a dielectric medium, any air voids present near a junction reduce capacitance. It has been shown that, for an electrode width of 640 m, femto-Farad measurement resolution is sufficient to resolve partial voiding of a junction region in a 25 m dielectric layer [29].…”
Section: Sensor Descriptionmentioning
confidence: 99%
“…A near-field focusing sensor with very small separation between electrode planes (20 m -500 m) has been proposed for in situ characterization of thin dielectric layers [23]. For small electrode plane 4 separation, moderate electrode pitch is sufficient to guarantee independent detection zones at each electrode junction, even when inactive electrodes are allowed to float during measurement [24]. Virtual grounding of inactive electrodes during sequential actuation allows for detection zones to be approximately independent even with a smaller electrode pitch by damping the electric field outside the vicinity of the actuated junction [23].…”
Section: Introductionmentioning
confidence: 99%